KEHIDUPAN SOSIAL EKONOMI PEMULUNG BATUBARA DI KOTA SAWAHLUNTO (1998-2012) - Sari, Endang Kumala; Husnita, Liza; Zulfa, Zulfa (Pendidikan Sejarah, 2013)
ABSTRACTIncreasingly volatile economic crisis in 1998 which lead to uncontrolled widespread panic to the people of Indonesia, is no exception Sawahlunto. With the coal mining company in Indonesia Ombilin oldest. Can directly improve the economy Sawahlunto. With the government regulations that allow the city / county on investments including mining permit. Thus emerged the CV or KP ( Mining ). So the impact of the presence of coal scavengers that create jobs and increase their incomes. With the goal is ( 1 ) knowing the background of Coal Scavengers Sawahlunto chose the profession, ( 2 ) determine the socio-economic life of Coal Scavengers. Based on the above research objective methods used in this study is the historical method. Producer encountered during this study were : ( 1 ) Heuristic , ( 2 ) Criticism Sources , ( 3 ) Interpretation, ( 4 ) Historiography ( presentation of research results in the form of a scientific paper or thesis. Research shows that the background is a scavenger chose the profession because of a desire to meet the necessities of life, the absence of other jobs, in addition to the economic life of coal scavengers depending on the circumstances when there is a CV that opening of new mines, they can still earn a living. Level of well-being can not be separated from scavengers salary or wages received. Based on the research it can be concluded, that the income derived by coal scavengers ranged from Rp 350.000, - to Rp 400,000. Coal scavengers social life is also good, both among fellow pickers, truckers up to the owner of the mine. Keywords : social , economic, coal scavengers